Komparasi Penerapan Algoritma C4.5 dan Naïve Bayes untuk Ketepatan Waktu Pengiriman Barang Pada PT. Rtrans Logistik Artamandiri - Azzahra, Yasmin Aulia; Akbar, Yuma (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The logistics industry faces significant challenges in maintaining the punctual delivery of goods, which is a critical factor in enhancing customer satisfaction and reducing operational costs. This research aims to compare the effectiveness of the C4.5 and Naïve Bayes algorithms in analyzing the factors that influence delivery punctuality at PT. Rtrans Logistics Artamandiri. A dataset comprising 1,000 shipping records and 13 relevant attributes was utilized to assess each algorithm’s predictive performance in supporting decision-making processes related to delivery efficiency. The findings reveal that the C4.5 algorithm achieves a higher accuracy of 95.00%, compared to the Naïve Bayes algorithm, which reached an accuracy of 91.00%. Furthermore, this study highlights the importance of selecting the appropriate algorithm in logistics management to enhance operational efficiency and customer satisfaction. The results of this research are expected to provide a foundation for strategic decision-making in the field of goods delivery, particularly in optimizing delivery timeliness.